Pengaruh Kualitas Pelatihan, Pemanfaatan Teknlogi Informasi dan Komitmen Organisasi Terhadap Keterandalan Pelaporan Keuangan Pemerintah Desa - Kadek Ayu Indrayani; Desak Nyoman Werastuti (Universitas Pendidikan Ganesha, 2021)
This study aims to determine the effect of training quality, use of information technology, and organizational commitment to the reliability of village government financial reporting. This study uses a quantitative approach using a questionnaire which is measured using a Likert scale. The population in this study were village officials consisting of the Village Head, Village Secretary, and Head of Financial Affairs in Buleleng Regency with a total of 387 village officials. The sampling method in this study is simple random sampling technique with a total sample of 197 respondents. The data analysis technique in this study used multiple linear regression with the help of the SPSS 24.0 for Windows program. The results of this study indicate that: (1) the quality of training has a positive effect on the reliability of village government financial reporting; (2) the use of information technology has a positive effect on the reliability of village government financial reporting; (3) organizational commitment has a positive effect on the reliability of village government financial reporting.